Cardiac Autonomic Dysfunction and Incidence of de novo Atrial Fibrillation: Heart Rate Variability vs. Heart Rate Complexity - Wessel, Niels; Berg, Karsten; Kraemer, Jan F.; Gapelyuk, Andrej; Rietsch, Katrin; Hauser, Tino; Kurths, Jürgen; Wenzel, Dave; Klein, Norbert; Kolb, Christof; Belke, Roberto; Schirdewan, Alexander; et al. (Frontiers in Physiology, 2020)
BACKGROUND: The REACT DX registry evaluates standard therapies to episodes of long-lasting atrial tachyarrhythmias and assesses the quality of sensing and stability of the lead and the implantable cardioverter defibrillator (ICD) (BIOTRONIK Lumax VR-T DX and successors) over a one year follow-up period. OBJECTIVE: To study the association between the risk of de novo device-detected atrial fibrillation (AF), the autonomic perturbations before the onset of paroxysmal AF and a seven-days heart rate variability (7dHRV) one month after ICD implantation. METHODS: The registry consists of 234 patients implanted with an ICD, including 10 with de novo long-lasting atrial tachyarrhythmias with no prior history of AF. The patients were matched via the propensity-score methodology as well as for properties directly influencing the ECGs recorded using GE CardioMem CM 3000. Heart rate variability (HRV) analysis was performed using standard parameters from time- and frequency-domains, and from non-linear dynamics. RESULTS: No linear HRV was associated with an increased risk of AF (p=n.s.). The only significant approach was derived from symbolic dynamics with the parameter 'forbidden words' which distinguished both groups on all seven days of measurements (p<0.05), thereby quantifying the heart rate complexity (HRC) as drastically lower in the de novo AF group. CONCLUSION: Cardiac autonomic dysfunction denoted by low HRC may be associated with higher AF incidence. For patients with mild to moderate heart failure, standard HRV parameters are not appropriate to quantify cardiac autonomic perturbations before the onset of AF. Further studies are needed to determine the individual risk for AF that would enable interventions to restore autonomic balance in the general population.